Gravity anomalies and spatial variations of flexural rigidity at mountain ranges - Stewart, J; Watts, A (1997)
New continent-wide compilations of gravity and topography data have been used to determine, spatial variations in the long-term mechanical properties of the foreland lithosphere at mountain ranges. In the southern Appalachians, a large elastic thickness Te (in the range 40-70 km) is required with variation only along the length of the mountain range. To explain the Appalachian Bouguer gravity anomaly "high", a subsurface load and crustal thinning are necessary. For the Andes, Te varies in the range 5-85 km perpendicular and parallel to the length of the mountain range. In the Alps, Te is high in the French Alps and then decreases in the western Swiss Alps and increases toward the eastern Alps. In the Romanian Carpathians, Te variations in the range 5-20 km are found. Although the thermal state, curvature, and inelastic yielding may play some role, these variations in Te are interpreted as the result of inheritance of the thermal and mechanical properties of foreland lithosphere. Inheritance plays a role in influencing the development of the next plate tectonic event. At mountain ranges, preexisting strength variations offer some control on tectonic style, the geometry of fold and thrust belts, and the stratigraphic patterns that develop in the adjacent foreland basin. Foreland lithosphere is involved in a cycle of events that began with continental rifting and passive margin formation and ended in continental collision. Compilations of Te from continental rifts, passive margins, and foreland lithosphere show large variations. The lowest values are associated with rifts, margins, and foreland lithosphere which has recently been been involved in continental breakup. The highest values are associated with foreland lithosphere for which a long time has elapsed since the previous rifting event. We speculate that continental lithosphere undergoes some form of strength recovery. Copyright 1997 by the American Geophysical Union.